The Formation of Gay Space in Joko Anwar’s Arisan! - Noor, Marzita Mohamed; Seach, Jin Beng (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2022)
Although the notion of gay space started out as a cultural geographic study that predominantly focused on Western countries where gay visibility was high, more scholars have begun to show keenness in tracing the existence of gay space in Asian regions in recent years. This article traces the formation of gay space in Jono Anwar’s 2003 movie Arisan!. Set in modern day Indonesia where homosexuality is still deeply frowned upon, the movie explores how the male protagonist - Sakti struggles to come to terms with his own homosexuality in a world governed by heteronormativity. This study argues that the gay space in Arisan! is not formed by merely portraying the gay characters in a positive light but rather, by toppling the heteronormative structures that shaped the core of sexual hegemony as portrayed in the movie. This study examines how the formidable heteronormative structures are destabilized by toxic masculinity, toxic femininity, and the problematizing of heterosexual world for the purpose of making room for the formation of gay space.